Dreams and nightmares in personality disorders - Schredl, Michael (Current psychiatry reports, 2016)
Although the relationship between dreaming and psychopathology has been studied quite extensively, research on dreaming in patients with personality disorders has been very scarce. In patients with borderline personality disorder, negatively toned dreams and heightened nightmare frequency have been found - characteristics not determined by co-morbid depression or posttraumatic stress disorder. The review includes suggestions for future studies as the existing results clearly indicate that this line of research is most interesting. Lastly, clinical recommendations especially regarding the treatment of the often found co-morbid nightmare disorder will be given.
Gesehen am 07.02.2019